PEMEROLEHAN BAHASA PERTAMA MELALUI PIVOT GRAMMAR - Syahfitri Purnama (Universitas Nasional, 2016)
ABSTRACTThe purpose of this study was to assess the child's first language syntax acquisition two years of age through thepivot grammar. The first source of this research is Francesca Sophia, Superkids student, Kemang, South Jakarta.This research used descriptive analysis and data collected, captured, recorded, transcribed, and analyzed. Theresults of this study are: Keywords: first language acquisition, pivot grammar, Speech production development